P-189 Association between iDAScore v1.0, senior embryologists' grading and euploidy in 546 blastocysts obtained during 189 PGT-A cycles. (30th June 2022) - Casciani, V; Cimadomo, D; Trio, S; Chiappetta, V; Innocenti, F; Iussig, B; Alviggi, E; Canosa, S; Barnocchi, N; Maggiulli, R; Berntsen, J; Kragh, M.F; et al.
Abstract: Study question: Is (intelligent data analysis) iDAScore v1.0 associated with euploidy at the blastocyst stage? Summary answer: iDAScore v1.0 significantly correlated with euploidy (maternal age-adjusted OR:1.3 and AUC:0.72). Euploid blastocysts were ranked highest in ca.70% of the cohorts with both diagnoses. What is known already: With machine learning and artificial intelligence (AI) implementation in IVF, several studies have been published mostly aimed at providing standardized and reproducible tools for gamete/embryo assessment and selection. Several of the proposed models might not be generally applicable due to their development on only a single center, small sample size and poor representation of the numerous clinical scenarios. Furthermore, the evidence has been rarely confirmed prospectively and/or in multicenter studies. Lately, the EmbryoScope+ has incorporated the iDAScore v1.0. This algorithm scores the chance of embryo implantation based on the video of blastocyst development and with no need for timing annotations. Study design, size, duration: Interim analysis of a prospective study. Between April-December 2021, 189 preimplantation-genetic-testing (PGT) cycles (maternal age:38.4±4yr) with ≥1 blastocyst (N = 546 blastocysts, mean±SD:2.9±1.8, range:1-13) were included. We aimed at blindly analyzing the correlation between iDAScore v1.0 and (i) blastocyst quality estimated by senior embryologists, (ii) day of blastocyst full-expansion, (iii) chromosomal constitution diagnosed by NGS on a trophectoderm biopsy, (iv) the blastocyst to prioritize for transfer within cohorts with ≥2 blastocysts. Participants/materials, setting, methods: Undisturbed culture was conducted in the EmbryoScope+. Assisted hatching was not performed and only fully-expanded blastocysts were biopsied. Morphology was assessed by 2 senior embryologists based on Gardner criteria. Average iDAScores were reported for the following groups: (i)excellent (AA)/good (AB, BA)/average (BB, AC, CA)/poor-quality (CC, BC, CB) blastocysts, (ii)day5/6/7 blastocysts, (iii)euploid/aneuploid/complex aneuploid blastocysts. Lastly, we reported how often the highest iDAScore corresponded to the highest ranked morphology (N = 143 cycles with ≥2 blastocysts) and/or euploid blastocysts (N = 79 cycles with both diagnoses). Main results and the role of chance: In the study period, 546 blastocysts (iDAScore: 6.9±2.0, 2-9.7) were biopsied. The iDAScore was significantly different (Kruskal-Wallis<0.01) across blastocysts graded excellent (N = 256, 46.9%; 8.1±1.3, 2.5-9.7), good (N = 97, 17.7%; 6.9±1.6, 2.3-9.5), average (N = 75, 13.9%; 5.8±1.4, 2.9-8.7) and poor (N = 118, 21.5%; 4.8±1.6, 2-8.8). A significant difference (Kruskal-Wallis<0.01) was also found for the day of full-expansion (day5: N = 184, 33.9%, 8.8±0.8, 4.3-9.7; day6: N = 324, 59.1%, 6.0±1.6, 2.2-9.1; day7: N = 38, 6.9%, 4.6±1.6, 2-7.8). Euploid blastocysts (N = 178, 32.6%) had a significantly higher (Kruskal-Wallis<0.01) iDAScore (7.5±1.7, 2.4-9.6) than both simple (N = 209, 38.3%, 6.7±2.1, 2.1-9.7) and complex aneuploid blastocysts (N = 159, 29.1%, 6.3±2.0, 2-9.4). The logistic regression adjusted for maternal age highlighted a multivariate-OR 1.3, 95%CI 1.18-1.45, adjusted-p<0.01 for the association between iDAScore v1.0 and euploidy. The Receiver-Operating-Characteristic (ROC) curves outlined similar performance in predicting euploidy among the models encompassing iDAScore v1.0 adjusted for maternal age (AUC: 0.72, 95%CI 0.67-0.76, p < 0.01) or blastocyst quality (defined by senior embryologists) plus day of biopsy also adjusted for maternal age (AUC: 0.73, 95%CI 0.69-0.78, p < 0.01). iDAScore v1.0 and embryologists ranked the same blastocyst highest in 123 of 143 cycles with ≥2 blastocysts (86%). The highest ranked blastocyst according to iDAScore was a euploid blastocyst in 54 of the 79 cycles (68%) containing both euploid and aneuploid blastocysts. Limitations, reasons for caution: The main purpose of iDAScore v1.0, for which the algorithm was trained, is implantation prediction of untested blastocysts. Thus, once the sample size of this blinded prospective study will be large enough, we will also examine the association between iDAScore v1.0 and the implantation of euploid blastocysts. Wider implications of the findings: The similar predictivity on euploidy reported between subjective senior embryologists' grading and objective AI-powered iDAscores is promising in view of IVF automation and standardization. This is especially relevant since iDAScore v1.0 has not been trained yet to specifically predict euploidy, and its future versions could be fine-tuned accordingly. Trial registration number: Not Applicable